GeneMatcher Aids in the Identification of a New Malformation Syndrome with Intellectual Disability, Unique Facial Dysmorphisms, and Skeletal and Connective Tissue Abnormalities Caused by De Novo Variants in HNRNPK. Issue 10 (6th August 2015) - Au, P. Y. Billie; You, Jing; Caluseriu, Oana; Schwartzentruber, Jeremy; Majewski, Jacek; Bernier, Francois P.; Ferguson, Marcia; Valle, David; Parboosingh, Jillian S.; Sobreira, Nara; Innes, A. Micheil; Kline, Antonie D.
<x xml:space="preserve">Abstract</x> We report a new syndrome due to loss of function variants in the heterogeneous nuclear ribonucleoprotein K gene (HNRNPK, OMIM *600712). We describe two probands, both of whom have intellectual disability, a shared unique craniofacial phenotype, and connective tissue and skeletal abnormalities. The identification of this syndrome was made possible by a new online tool, GeneMatcher, which facilitates connections between clinicians and researchers based on shared interest in candidate genes, and highlights the newer paradigm of "reverse phenotyping."